Zanubrutinib Versus Ibrutinib in Relapsed/Refractory Chronic Lymphocytic Leukemia and Small Lymphocytic Lymphoma: Interim Analysis of a Randomized Phase III Trial. Issue 5 (10th February 2023) - Hillmen, Peter; Eichhorst, Barbara; Brown, Jennifer R.; Lamanna, Nicole; O'Brien, Susan M.; Tam, Constantine S.; Qiu, Lugui; Kazmierczak, Maciej; Zhou, Keshu; Šimkovič, Martin; Mayer, Jiří; Gillespie-Twardy, Amanda; et al.
Abstract : PURPOSE: Zanubrutinib is a potent, irreversible next-generation Bruton tyrosine kinase (BTK) inhibitor designed to maximize BTK occupancy and minimize off-target kinase inhibition. We hypothesized that complete/sustained BTK occupancy may improve efficacy outcomes and increased BTK specificity may minimize off-target inhibition-related toxicities. PATIENTS AND METHODS: ALPINE (ClinicalTrials.gov identifier: NCT03734016 ) is a global, randomized, open-label phase III study of zanubrutinib versus ibrutinib in patients with relapsed/refractory chronic lymphocytic leukemia. The primary end point was investigator-assessed overall response rate (ORR). The preplanned interim analysis was scheduled approximately 12 months after the first 415 patients were enrolled. RESULTS: Between November 1, 2018, and December 14, 2020, 652 patients were enrolled. We present the interim analysis of the first 415 enrolled patients randomly assigned to receive zanubrutinib (n = 207) or ibrutinib (n = 208). At 15 months of median follow-up, ORR (partial or complete response) was significantly higher with zanubrutinib (78.3%; 95% CI, 72.0 to 83.7) versus ibrutinib (62.5%; 95% CI, 55.5 to 69.1; two-sided P < .001). ORR was higher with zanubrutinib versus ibrutinib in subgroups with del(17p)/ TP53 mutations (80.5% v 50.0%) and del(11q) (83.6% v 69.1%); 12-month progression-free survival in all patients was higher with zanubrutinib (94.9%) versus ibrutinib (84.0%; hazard ratio, 0.40; 95% CI, 0.23 to 0.69). Atrial fibrillation rate was significantly lower with zanubrutinib versus ibrutinib (2.5% v 10.1%; two-sided P = .001). Rates of cardiac events, major hemorrhages, and adverse events leading to treatment discontinuation/death were lower with zanubrutinib. CONCLUSION: Zanubrutinib had a significantly higher ORR, lower atrial fibrillation rate, and improved progression-free survival and overall cardiac safety profile versus ibrutinib. These data support improved efficacy/safety outcomes with selective BTK inhibition.